2016
DOI: 10.1167/16.9.11
|View full text |Cite
|
Sign up to set email alerts
|

Visual field restorative rehabilitation after brain injury

Abstract: About 20%-30% of patients undergoing neurological rehabilitation report visual field defects, one of the most frequent of which is homonymous hemianopsia (loss of the same half of the visual field in both eyes). There is still no consensus as to whether homonymous hemianopsia is best treated in a restorative or compensatory manner. The aim of this review is to describe the effects of restorative rehabilitation, whose long-term efficacy is still being debated. We analyzed 56 articles describing the use of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 109 publications
0
22
0
Order By: Relevance
“…Our previous paper 42 ) strongly suggest that blindsight rehabilitation improves the processing of visual stimuli, so it is possible that stimulation of associative areas could facilitate this processing mechanism.…”
Section: Discussionmentioning
confidence: 95%
“…Our previous paper 42 ) strongly suggest that blindsight rehabilitation improves the processing of visual stimuli, so it is possible that stimulation of associative areas could facilitate this processing mechanism.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have reported that repeated stimulation synchronizes neuronal firing in the same areas, and, as this synchronization requires attentional activation, it leads to synaptic plasticity. 4,7 We think that 3D vision rehabilitation combined with this treatment increases this plasticity in our study. Perimetry evaluations made at the end of the study support these results.…”
Section: Discussionmentioning
confidence: 59%
“…A An na ah h t ta ar r K Ke e l li i m me e l le er r: : Travmatik beyin hasarı; görme alanı defekti; görme tedavisi; üç boyutlu gözlük Arif Uğur TAMKAN a , Ebru KARACA UMAY a been carried out, there is still no consensus on an effective method to treat TBI-related visual field loss. 4,5 We presented three-dimensional (3D) glasses and computer-based attention treatment which is used as a new treatment method in two patients with visual field defect and severe TBI (Written consent was obtained from patients and their relatives).…”
mentioning
confidence: 99%
“…Repeated in daily sessions, it may modulate brain network plasticity. After unilateral occipital strokes, cortical transcranial direct current stimulation combined with rehabilitation enhanced recovery of homonymous hemianopic visual field defects (Gall et al, 2015 ; Matteo et al, 2016 ).…”
Section: Innovations and Perspectivesmentioning
confidence: 99%